2017
DOI: 10.1242/dev.145698
|View full text |Cite
|
Sign up to set email alerts
|

The E2A splice variant E47 regulates the differentiation of projection neurons via p57(KIP2) during cortical development

Abstract: During corticogenesis, distinct classes of neurons are born from progenitor cells located in the ventricular and subventricular zones, from where they migrate towards the pial surface to assemble into highly organized layer-specific circuits. However, the precise and coordinated transcriptional network activity defining neuronal identity is still not understood. Here, we show that genetic depletion of the basic helix-loop-helix (bHLH) transcription factor E2A splice variant E47 increased the number of Tbr1-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 89 publications
(128 reference statements)
1
26
0
Order By: Relevance
“…For example, one study using knockout mice deficient for E12 or E47 revealed that E47 is essential for developmental progression at the pre-pro-B-cell stage, whereas E12 is dispensable for early B-cell development, commitment, and maintenance (Beck et al 2009). In cortical neurogenesis, E47 is required for proper neuronal differentiation and layer-specific localization, whereas E12 is dispensable for early corticogenesis (Pfurr et al 2017). These reports suggest that TCF3 AS plays an important role in a variety of developmental processes.…”
mentioning
confidence: 99%
“…For example, one study using knockout mice deficient for E12 or E47 revealed that E47 is essential for developmental progression at the pre-pro-B-cell stage, whereas E12 is dispensable for early B-cell development, commitment, and maintenance (Beck et al 2009). In cortical neurogenesis, E47 is required for proper neuronal differentiation and layer-specific localization, whereas E12 is dispensable for early corticogenesis (Pfurr et al 2017). These reports suggest that TCF3 AS plays an important role in a variety of developmental processes.…”
mentioning
confidence: 99%
“…During embryogenesis, E47 promotes cortical plate neural development and, in adult neural precursor cells, represses an astrocyte-specific gene program. In contrast, the E-protein antagonist Id3 orchestrates BMP2-induced astrocyte differentiation (Pfurr et al 2017). Upon cortical brain injury, Id3 is induced by BMP2 to neutralize E47 activity and promote astrocyte differentiation (Bohrer et al 2015).…”
Section: E Proteinsmentioning
confidence: 99%
“…Genome-wide ChIP-seq studies have established that the preferential E-box motifs bound by ASCL1, E47 and NEUROG1 correspond respectively to CAGCTG ( Castro et al, 2011 ; Borromeo et al, 2014 ), CAGSTG (where S stands for C or G: Lin et al, 2010 ; Pfurr et al, 2017 ) and CADATG (where D stands for A, G or T: Seo et al, 2007 ; Madelaine and Blader, 2011 ). In light of these intrinsic preferences, we tested how E47 modulates the abilities of ASCL1 and NEUROG1 to bind to DNA and activate transcription in different E-box contexts ( Figure 6A and Figure 6—figure supplement 2A ).…”
Section: Resultsmentioning
confidence: 99%